What Are You Anxious About? Examining Subjects of Anxiety during the COVID-19 Pandemic - Chen, Lucia L.; Wilson, Steven R.; Lohmann, Sophie; Negraia, Daniela V. (Proceedings of the International AAAI Conference on Web and Social Media, 2023)
COVID-19 poses disproportionate mental health consequences to the public during different phases of the pandemic. We use a computational approach to capture the specific aspects that trigger the public's anxiety about the pandemic and investigate how these aspects change over time. First, we identified nine subjects of anxiety (SOAs) in a sample of Reddit posts (N=86) from r/COVID19_support using the thematic analysis approach. Then, we quantified Reddit users' anxiety by training algorithms on a manually annotated sample (N=793) to annotate the SOAs in a larger chronological sample (N=6,535). The nine SOAs align with items in various recently developed pandemic anxiety measurement scales. We observed that Reddit users' concerns about health risks remained high in the first eight months since the pandemic started. These concerns diminished dramatically despite the surge of cases occurring later. In general, users' language disclosing the SOAs became less intense as the pandemic progressed. However, worries about mental health and the future steadily increased throughout the period covered in this study. People also tended to use more intense language to describe mental health concerns than health risk or death concerns. Our results suggest that the public's mental health condition does not necessarily improve despite COVID-19 as a health threat gradually weakening due to appropriate countermeasures. Our system lays the groundwork for population health and epidemiology scholars to examine aspects that provoke pandemic anxiety in a timely fashion.